"Pesadillas de la noche, amanecer de silencio": Miguel Méndez and Margarita Oropeza - Debra A. Castillo (Studies in 20th & 21st Century Literature, 2001)
In many border-related discussions—whether philosophical, anthropological, critical, or fictional—there are typical themes or narrative tics: allusions to the flexible geography that makes the border region both an isolated territory and an analogue for the postmodern condition, the puzzlement over how to understand the role of the "maquiladoras" 'assembly plants' and the area's industrial boom, the awareness of a vast movement of people both north and south, a persistent and nagging phobia about feminization, and about female sexuality. In this paper I will explore these concerns with reference to two novels: Arizonan Miguel Méndez's well-known 1974 novel Peregrinos de Aztlán (Pilgrims in Aztlán), a fragmentary fiction set in Tijuana, and Sonoran Margarita Oropeza's 1992 novel Después de la montaña (After the Mountain), which begins with a woman crossing the border at San Isidro and concerns itself with her life as a migrant in California. Méndez's nightmare-wracked re-invention of the cacaphonous voices of the many migrant souls who define Tijuana by night finds its counterpart in Oropeza's focus on a single migrant women whose meditations on her mostly domestically oriented dreams jostle against her literal and metaphorical silencing in both U.S. and Mexican communities. At the same time, each novel evokes a geopolitical and cultural space of multiple crossings, one that is far more heterogeneous than conventionally transnational.
Keywords: border; Miguel Méndez; Margarita Oropeza; maquiladoras; postmodern condition; territory; identity; gragmentation; fiction; Peregrinos de Aztlán; Después de la montaña; migrant; geopolitics; transnational